2003
DOI: 10.1111/1467-9248.00419
|View full text |Cite
|
Sign up to set email alerts
|

Legitimacy Problems in Deliberative Democracy

Abstract: The classic accounts of deliberative democracy are also accounts of legitimacy: ‘that outcomes are legitimate to the extent they receive reflective assent through participation in authentic deliberation by all those subject to the decision in question’ ( Dryzek, 2001, p. 651 ). And yet, in complex societies deliberative participation by all those affected by collective decision-making is extremely implausible. There are also legitimacy problems with the demanding procedural requirements which deliberation impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
179
0
19

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(199 citation statements)
references
References 39 publications
1
179
0
19
Order By: Relevance
“…The deliberative democratic ideal is impossible to fulfil in its purest sense (Benhabib 1996;Goodin 2000;Parkinson 2003). In an ideal situation legitimacy comes from "the free and unconstrained deliberation of all about matters of common concern" (Benhabib 1996).…”
Section: Citizens' Panel and Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…The deliberative democratic ideal is impossible to fulfil in its purest sense (Benhabib 1996;Goodin 2000;Parkinson 2003). In an ideal situation legitimacy comes from "the free and unconstrained deliberation of all about matters of common concern" (Benhabib 1996).…”
Section: Citizens' Panel and Participationmentioning
confidence: 99%
“…John Parkinson (2003) has suggested that the group of citizens in a deliberative democratic setting should be less than 20 persons, otherwise deliberative conversation and reason will be replaced by speech-making and rhetorical appeals. A possible solution to the problem of scale, perhaps better described as the problem of deliberative economy, is also a recruiting procedure to select representative participants by lot.…”
Section: Citizens' Panel and Participationmentioning
confidence: 99%
“…Esto implica que la representación no debe ser pensada al modo del fideicomiso, pues el ciudadano no se desentiende de la labor que realiza el representante ni éste deja de rendir cuentas en el período transcurrido entre las elecciones, debido a la deliberación continuada entre ciudadanos y representantes. 39 …”
Section: Los Detractores De La Participación Directaunclassified
“…Not everyone agrees that deliberation alone can deliver sound policy (Sanders, 1997;Dryzek 2000;Parkinson 2003). Nonetheless, most admit the need for views that are the product of deliberation rather than statements of opinion, for policy has to be justified upon a stronger basis than its simply being what most people want.…”
Section: Barriers To Participationmentioning
confidence: 99%